Sejarah dan Perkembangan Tradisi Mogang di Batu Bara - Khoiruddin, Rudi; Harahap, Nursapia; Hamdani, Muhammad Faisal (Warisan: Journal of History and Cultural Heritage, 2020)
This article discusses the history of the Mogang tradition in Batu Bara. This tradition has been carried out since the 1700s. In Batu Bara, this tradition has been a hereditary culture since the Kedatuan era until now. Batu Bara is an area located on the eastern coast of Sumatra and faces the Strait of Malacca, precisely at the mouth of the Batu Bara River. This study uses the historical method in four writing steps, namely; heuristics, verification or criticism, interpretation, and historiography, with a cultural approach. Based on the information the author got, in Batu Bara there are ancient tombs that are thought to be from the 18th century. This proves that, there were already human settlements in the area before the 18th century. Mogang itself means slaughtering or slaughtering. Usually, this tradition is carried out by Kedatuan in welcoming the Holy month of Ramadan and Eid al-Fitr. In this tradition, Kedatuan slaughtered livestock to be distributed to the community. Along with its development, this tradition also has economic, social, cultural and religious values.